2013
DOI: 10.1371/journal.pone.0083282
|View full text |Cite|
|
Sign up to set email alerts
|

In the Absence of Animacy: Superordinate Category Structure Affects Subordinate Label Verification

Abstract: Theoretical accounts as well as behavioral studies reporting animacy effects offer inconsistent and sometimes contradictory results. A possible explanation for these inconsistencies may be inadvertent biases in the stimuli selected for test – with category-specific effects driven by characteristics of test stimuli other than animacy per se. In this study, we pit animacy against feature structure (intra-item variability), in a picture-word matching task. For unimpaired adults, regardless of whether objects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Some studies have found a processing difference between animate and inanimate entities, at both a behavioral and a neural level (Martin, Wiggs, Ungerleider, & Haxby, 1996; Perani et al, 1995, 1999). Other studies have failed to replicate this finding (Devlin et al, 2002; Ilić, Ković, & Styles, 2013; Pilgrim, Fadili, Fletcher, & Tyler, 2002; Tyler, Bright, et al, 2003).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Some studies have found a processing difference between animate and inanimate entities, at both a behavioral and a neural level (Martin, Wiggs, Ungerleider, & Haxby, 1996; Perani et al, 1995, 1999). Other studies have failed to replicate this finding (Devlin et al, 2002; Ilić, Ković, & Styles, 2013; Pilgrim, Fadili, Fletcher, & Tyler, 2002; Tyler, Bright, et al, 2003).…”
mentioning
confidence: 95%
“…Studies that reported differences in processing of animate and inanimate entities used only these two categories (Martin, Wiggs, Ungerleider, & Haxby, 1996; Perani et al, 1995, 1999). Studies that have failed to demonstrate processing differences between animates and inanimates typically have used several categories of objects to instantiate animate and inanimate classes (Devlin et al, 2002; Ilić et al, 2013; Pilgrim et al, 2002; Tyler, Bright, et al, 2003). For example, animals and fruits were treated as living or natural kinds, while tools and vehicles were nonliving, that is, manmade objects (Devlin et al, 2002).…”
mentioning
confidence: 99%
“…Such an explanation is also consistent with the overlapping semantic feature hypothesis (McRae et al, 1997) that suggests animals may be more memorable than objects because animals share more overlapping features (e.g., fur, four legs, teeth) relative to objects, which tend to have wider-ranging features (e.g., features of different musical instruments such as trumpets and guitars have less featural overlap). This hypothesis is supported by studies showing benefits of greater feature and neural global pattern overlap for subsequent memory (Ilic et al, 2013;Xiao et al, 2016). Overlapping semantic features can explain animacy and reverse animacy effects by drawing on the spreading-activation theory of semantic memory (Collins and Loftus, 1975) that posits concepts activate other semantically-related concepts in memory proportional to the degree of relatedness.…”
Section: Methodsmentioning
confidence: 94%
“…Some studies have reported behavioral and/or neurological differences in response to animate and inanimate stimuli (Perani et al, 1995;Martin et al, 1996;Perani et al, 1999). Other studies have failed to replicate these findings (Devlin et al, 2002;Pilgrim et al, 2002;Tyler et al, 2003;Ilić et al, 2013). The linguistic encoding of animacy has been shown to affect many different aspects of psychological functioning, including the processing of relative clauses (Mak et al, 2002;Traxler et al, 2005;Gennari et al, 2012); attentional mechanisms (Bugaiska et al, 2019); the detection of semantic violations in language (Grewe et al, 2006;Szewczyk and Schriefers, 2011); the learning of artificial languages (Vihman et al, 2018); word recognition (Bonin et al, 2019) and the ability to recall words (Bonin et al, 2015;VanArsdall et al, 2015;Bugaiska et al, 2016;Serra, 2016, 2018;Nairne et al, 2017;Kazanas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%